PENGARUH INOVASI DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN MELALUI PRODUK BARU PADA PT. PRAPTA MAKASSAR - Erniati Erniati; Buyung Romadhoni; Andi Mappatompo (COMPETITIVENESS, 2021)
This study aims to determine the extent of the influence of innovation and product quality on customer satisfaction through new products. This type of research uses a quantitative approach. Data collection techniques through online questionnaires to 180 respondents. Hypothesis testing uses path analysis with the help of AMOS 21 software.The results showed that the innovation variable had a significant positive effect on new products; Product quality has a significant positive effect on new products; Innovation has a significant positive effect on customer satisfaction; Product quality has no significant positive effect on customer satisfaction; New products have a significant effect on customer satisfaction; Innovation has a significant positive effect on customer satisfaction through new products and product quality has a significant positive effect on customer satisfaction through new products. Keywords: Innovation, Product Quality, Customer satisfaction, New produduct.